Effects of PNPLA3 I148M on hepatic lipid and very‐low‐density lipoprotein metabolism in humans - Borén, Jan; Adiels, Martin; Björnson, Elias; Matikainen, Niina; Söderlund, Sanni; Rämö, Joel; Henricsson, Marcus; Ripatti, Pietari; Ripatti, Samuli; Palotie, Aarno; Mancina, Rosellina M.; Ainola, Mari; et al. (Journal of internal medicine, 2022)
Background The phospholipase domain‐containing 3 gene (PNPLA3)‐148M variant is associated with liver steatosis but its influence on the metabolism of triglyceride‐rich lipoproteins remains unclear. Here, we investigated the kinetics of large, triglyceride‐rich very‐low‐density lipoprotein (VLDL), (VLDL1), and smaller VLDL2 in homozygotes for the PNPLA3‐148M variant. Methods and results The kinetics of apolipoprotein (apo) B100 (apoB100) and triglyceride in VLDL subfractions were analysed in nine subjects homozygous for PNPLA3‐148M and nine subjects homozygous for PNPLA3‐148I (controls). Liver fat was >3‐fold higher in the 148M subjects. Production rates for apoB100 and triglyceride in VLDL1 did not differ significantly between the two groups. Likewise, production rates for VLDL2‐apoB100 and ‐triglyceride, and fractional clearance rates for both apoB100 and triglyceride in VLDL1 and VLDL2, were not significantly different. Conclusions Despite the higher liver fat content in PNPLA3 148M homozygotes, there was no increase in VLDL production. Equally, VLDL production was maintained at normal levels despite the putative impairment in cytosolic lipid hydrolysis in these subjects.